Codonopsis pilosula polysaccharide alleviates rotenone-induced murine brain organoids death through downregulation of gene body DNA methylation modification in the ZIC4/PGM5/CAMTA1 axis - Haiyang Chen; Yichao Wen; Zhihua Yu; Xiling Du; Weidong Pan; Te Liu (Biochemistry and Biophysics Reports, 2024)
Here, the protective mechanism of Codonopsis pilosula polysaccharide (CpP) against mouse brain organoids (mBO) damage was analyzed, and the rotenone affected the genomic epigenetic modifications and physiological activity of mouse brain organoids was examined. Pathological experiments have shown that rotenone significantly damaged the subcellular organelles of mouse brain organoids. According to RRBS-Seq, rotenone significantly promoted gene body hypermethylation modifications in mouse brain organoids. Molecular biology experiments have confirmed that rotenone significantly promoted the hypermethylation modification of Zic4, Pgm5, and Camta1 gene bodies in mouse brain organoids, and their expression levels were significantly lower than those of the control group. Bioinformatic analysis suggested that multiple binding motif of transcription factors ZIC4 (Zinc finger protein of the cerebellum 4) were present at the promoters of both the Pgm5 (Phosphoglucomutase 5) and Camta1 (Calmodulin binding transcription activator 1) genes. When the expression of Zic4 was silenced, the proliferation of mouse brain organoids was significantly reduced and the expression level of PGM5 was also significantly decreased. In addition, Codonopsis pilosula polysaccharide treatment of mouse brain organoids significantly reduced the cytotoxicity of rotenone, promoted cell cycle progression, increased intracellular glutathione activity, significantly induced the demethylation modification of the Zic4, Pgm5, and Camta1 gene bodies, and promoted the high expression of ZIC4 and PGM5. Therefore, the study confirmed that Codonopsis pilosula polysaccharide alleviated rotenone-induced mouse brain organoids death by downregulating DNA gene bodies methylation modification of the Zic4/Pgm5/Camta1 axis.